Nano-hydroxyapatite dispersion liquid and application thereof

Treatment of nano-hydroxyapatite by carboxymethylcellulose sodium can be prepared with high stability and high dispersion nano-hydroxyapatite dispersion, which solves the problems of easy aggregation and low mechanical strength, and improves its application performance in environmental pollution treatment and agriculture.

CN119662266AActive Publication Date: 2025-03-21SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411753404.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-21
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Nanohydroxyapatite is limited in its practical application in environmental pollution treatment and agriculture due to its strong brittleness, low mechanical strength and easy aggregation.

Method used

By slowly adding the sodium carboxymethylcellulose solution to the nano-hydroxyapatite solution, stirring at room temperature, adjusting the pH to 9.0, and heating the reaction, the obtained nano-hydroxyapatite dispersion improves the stability of the nano-hydroxyapatite and reduces its agglomeration.

Benefits of technology

It improves the dispersion and particle uniformity of nano-hydroxyapatite, reduces particle size, enhances its ability to adsorb cadmium ions and promotes plant growth, simplifies the process flow and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662266A_ABST
    Figure CN119662266A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-hydroxyapatite dispersion liquid and an application thereof. Slowly adding the sodium carboxymethyl cellulose solution into the nano-hydroxyapatite solution, stirring at normal temperature, adjusting the pH value to 9.0, and heating for reaction to obtain the nano-hydroxyapatite dispersion liquid. The mass concentration of the sodium carboxymethyl cellulose solution is 0.5 wt%, and the concentration of the nano-hydroxyapatite solution is 0.3 g / L-0. 6 g / L. According to the preparation method, the dispersity and the particle uniformity of the nano-hydroxyapatite are improved, the particle size is reduced, the agglomeration phenomenon of hydroxyapatite particles in a dispersion medium is effectively eliminated, the nano-hydroxyapatite dispersion liquid which is high in dispersity, high in stability, safe and non-toxic is obtained, and the technological process is simplified. Most importantly, compared with an original method for improving dispersity by adding a dispersing agent in the synthesis process, the problems that the content of nano-hydroxyapatite dispersed by the original method is low, the synthesis process is complex, and transportation and practical application are inconvenient are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydroxyapatite, and in particular to a nano hydroxyapatite dispersion and application thereof. Background Art

[0002] As a material with good biocompatibility, nanohydroxyapatite (nHAP) is not only widely used in the medical field, but also has broad prospects in the field of environmental science. In the environmental field, nanohydroxyapatite can not only effectively treat and repair polluted water and soil, but also serve as a catalyst carrier and environmental functional material, providing an effective technical means for environmental protection. Due to its unique physical and chemical properties, nanohydroxyapatite is considered in many studies to be a functional material with outstanding removal effects on dyes, heavy metals and fluorine. The chemical composition of nHAP is composed of calcium ions and phosphate ions on the surface, which can interact with heavy metal ions to form complexes, thereby removing them through the adsorption process. A large number of studies have shown that the prepared nHAP has significant application prospects in treating cadmium-contaminated water. In addition to its wide application in the above-mentioned fields, nanohydroxyapatite is also used in the agricultural field to promote crop growth. Existing literature has shown that the efficiency of nanophosphate fertilizer is about 20% to 30% higher than that of traditional agricultural phosphate fertilizer. Compared with traditional phosphate fertilizers, plants absorb nanophosphate fertilizers faster, reducing fertilizer consumption and minimizing environmental pollution. More importantly, plant leaves have nanopores and stomatal openings, which can promote the direct absorption of nanofertilizers through deep penetration inside the leaves and improve the bioavailability of phosphorus fertilizers. The study found that the prepared rod-shaped nanohydroxyapatite was applied to pea seed germination and growth, and it was found that nanohydroxyapatite can increase the germination rate of pea seeds and promote plant growth. These studies show that nanofertilizers will become a sustainable alternative to traditional chemical fertilizers. Although nano-hydroxyapatite has shown good advantages in many fields, its practical application is limited due to its strong brittleness, low mechanical strength and easy aggregation. The patent with application number CN201610515008.0 discloses a nano-hydroxyapatite dispersion and its preparation process, wherein a calcium salt solution is added to an inorganic dispersant, and a nano-hydroxyapatite dispersion is prepared by hydrothermal reaction with a phosphate salt solution. The patent with application number CN201710284265.2 discloses a three-dimensional porous nano-hydroxyapatite and its preparation method, wherein a sodium carboxymethyl cellulose solution is mixed with a calcium solution, a phosphorus solution is added, and the sodium carboxymethyl cellulose is carbonized after calcination to obtain a three-dimensional porous nano-hydroxyapatite. Both of the above methods belong to the one-step direct synthesis of nano-hydroxyapatite. Although hydroxyapatite has good dispersibility, the amount of nano-hydroxyapatite dispersed each time is small, the synthesis process is complicated, the cost is high, and the actual transportation is inconvenient. Therefore, how to improve the stability of commercially available conventional nHAP, thereby minimizing its agglomeration and improving its application in cadmium pollution and crop growth, needs further exploration. Summary of the invention

[0003] In view of the above prior art, the object of the present invention is to provide a nano-hydroxyapatite dispersion and its application. The present invention treats nano-hydroxyapatite with sodium carboxymethyl cellulose, and the prepared nano-hydroxyapatite dispersion improves the stability of nano-hydroxyapatite in solution and alleviates the agglomeration of nano-hydroxyapatite. The treatment method of the present invention is simple and easy to mass produce and apply in practice.

[0004] To achieve the above object, the present invention adopts the following technical solution: In a first aspect of the present invention, a nano-hydroxyapatite dispersion is provided, wherein the nano-hydroxyapatite dispersion is prepared by the following method: The sodium carboxymethyl cellulose solution was slowly added to the nano-hydroxyapatite solution, and stirred at room temperature. The pH was adjusted to 9.0, and heated for reaction to obtain a nano-hydroxyapatite dispersion.

[0005] Preferably, the sodium carboxymethylcellulose solution is obtained by dissolving sodium carboxymethylcellulose powder in water and heating at 50-60° C.; the nano-hydroxyapatite solution is obtained by dispersing nano-hydroxyapatite in water and subjecting it to ultrasound.

[0006] Preferably, the particle size of the nano-hydroxyapatite is 60 nm.

[0007] Preferably, the volume ratio of the sodium carboxymethyl cellulose solution to the nano-hydroxyapatite solution is 1:1; and the stirring time is 3 hours.

[0008] Preferably, the mass concentration of the sodium carboxymethyl cellulose solution is 0.5wt%; the concentration of the nano-hydroxyapatite solution is 0.3g / L-0.6g / L.

[0009] Preferably, the method for adjusting the pH is to add alkali solution; the alkali solution is NaOH solution, and the concentration of the NaOH solution is 0-0.3 mol / L.

[0010] Preferably, the heating reaction is carried out at a temperature of 40-60° C. and for a time of 30-60 min.

[0011] The second aspect of the present invention provides the use of a nano-hydroxyapatite dispersion in any one of the following 1) to 3): 1) Improve the stability of nano-hydroxyapatite dispersion; 2) Adsorption of cadmium ions; 3) Promote plant growth.

[0012] Preferably, the step of improving the stability of the nano-hydroxyapatite dispersion includes: improving the dispersibility of the nano-hydroxyapatite, reducing the hydrodynamic diameter of the nano-hydroxyapatite, and increasing the absolute value of the zeta potential of the nano-hydroxyapatite.

[0013] Beneficial effects of the present invention: (1) The present invention reacts the nano-hydroxyapatite solution with sodium carboxymethyl cellulose, thereby improving the dispersibility and particle uniformity of the nano-hydroxyapatite, reducing the particle size, effectively eliminating the agglomeration of hydroxyapatite particles in the dispersion medium, and obtaining a highly dispersible, highly stable, safe and non-toxic nano-hydroxyapatite dispersion, thereby simplifying the process flow. Most importantly, compared with the original method of adding a dispersant during the synthesis process to improve the dispersibility, the present invention improves the problems of the original method of dispersing the nano-hydroxyapatite in a small amount, a complex synthesis process, and inconvenience in transportation and practical application.

[0014] (2) The dispersion prepared by the present invention solves the problems of easy agglomeration and poor dispersibility of nano-hydroxyapatite particles, giving nano-hydroxyapatite higher application performance and a wider range of applications, laying a good foundation for its application in soil and groundwater heavy metal pollution control and agricultural nano-hydroxyapatite additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 :Screening of sodium carboxymethyl cellulose concentration, including (A) absorbance curve, (B) optical density graph, (C) peak loss rate graph, (D) viscosity graph; Figure 2 :Screening of nano-hydroxyapatite concentration, including (A) daily sedimentation and dispersion graph, (B) optical density graph; Figure 3: Screening of dispersion pH, including (A) zeta potential change, (B) UV spectrum, (C) peak loss rate; Figure 4 : Hydrodynamic diameter of nanohydroxyapatite dispersions with different particle sizes; Figure 5 : Comparison of cadmium adsorption in each treatment group; Figure 6 : Average volume of pepper fruits in each treatment group. DETAILED DESCRIPTION

[0016] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0017] As described in the background technology section, the prior art generally adds a dispersant to calcium salt and phosphate salt, and then obtains nano-hydroxyapatite with good dispersibility through a high temperature reaction. However, this treatment method involves high temperatures, which will carbonize the dispersant, and the amount of nano-hydroxyapatite obtained by the reaction is too small, which is not suitable for industrial use.

[0018] Based on this, the purpose of the present invention is to provide a nano-hydroxyapatite dispersion and its application. Through research, it is found that the mass concentration of sodium carboxymethyl cellulose solution is 0.5wt%, the concentration of nano-hydroxyapatite solution is 0.3g / L-0.6g / L, the solution pH is adjusted to about 9.0, and heated at about 50°C to avoid excessively high temperature to form a gel. Such treatment can not only connect sodium carboxymethyl cellulose and nano-hydroxyapatite through hydrogen bonds, etc., but also further control the hydraulic diameter of nano-hydroxyapatite and improve the stability of nano-hydroxyapatite; thereby improving the ability of nano-hydroxyapatite to adsorb cadmium and promote plant growth.

[0019] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0020] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0021] Example 1 Sodium carboxymethyl cellulose CMC powder was added to distilled water, stirred continuously and fully dissolved by heating. The heating temperature was controlled at 55°C and cooled to room temperature to obtain a sodium carboxymethyl cellulose solution with a mass fraction of 0.5%. 60nm nano-hydroxyapatite particles were added to distilled water for ultrasonic mixing. The ultrasonic time was 4 minutes to uniformly disperse the nano-hydroxyapatite to obtain a nano-hydroxyapatite solution with a concentration of 0.45g / L. Under stirring conditions, the sodium carboxymethyl cellulose solution was slowly added to the nano-hydroxyapatite solution and stirred at room temperature for 3 hours to obtain a mixed solution. 0.1mol / L sodium hydroxide solution was added to the mixed solution, the pH value of the mixed solution was adjusted to 9.0, the mixed solution was heated at 50°C for 30 minutes, and the nano-hydroxyapatite dispersion was obtained after cooling.

[0022] Example 2 to Example 3, Comparative Example 1 to Comparative Example 11: The difference from Example 1 is that the concentration of the sodium carboxymethyl cellulose solution or the concentration of the nano-hydroxyapatite solution or the pH value is different, see Table 1 for details.

[0023] Table 1 Test Example 1: Screening Test (1) Screening of sodium carboxymethyl cellulose solution concentration The nano-hydroxyapatite dispersion prepared in Example 1 and Comparative Examples 1-2 was tested for relative absorbance, optical density and peak loss rate. The above test was measured by UV-visible spectrophotometer. Optical density = absorbance of the dispersion before centrifugation - absorbance of the supernatant after centrifugation of the dispersion. The UV peak loss rate is the percentage of the highest peak of the dispersion UV peak decreasing within 24 hours. The results are shown in Figure 1 .

[0024] The smaller the change of relative absorbance over time, the more stable the dispersion. Optical density is an important parameter to measure the stability of dispersion. The lower the optical density, the more stable the dispersion. The sedimentation of suspended particles in the dispersion can be measured by the loss rate of the supernatant peak of the dispersion. The higher the peak loss rate per unit time, the more the dispersion particles settle and the more unstable the dispersion. Figure 1 (A) ~ Figure 1 (C) in terms of relative absorbance, optical density and peak loss rate, comparative example 2 is the best. However, the content of sodium carboxymethyl cellulose in comparative document 2 is too high. Figure 1 (D) It can be seen that the viscosity of Comparative Example 2 is also the highest, and too high a viscosity is not convenient for the actual use of the dispersion. Therefore, considering the practical application and cost, the effect of Example 1 is the best.

[0025] (2) Screening of nanohydroxyapatite solution concentration The dispersions of Examples 2-3 and Comparative Examples 4-5 were tested for daily sedimentation and optical density. The results are shown in Figure 2 .

[0026] The daily sedimentation amount of the dispersion is determined by the weight method: a certain volume of dispersion is taken into a sedimentation bottle. Before starting sedimentation, V1 of the dispersion is filtered and dried, and its weight is recorded as m1. After free sedimentation for 24 hours, the supernatant of V1 is taken from the sedimentation bottle, filtered and dried, and its weight is recorded as m2. The daily sedimentation amount V=m1-m2.

[0027] Within a certain concentration range, the increase in the concentration of nano-hydroxyapatite particles in the dispersion will increase the number of particles with the same type of charge in the solution, and the electrostatic repulsion between the particles will be enhanced. This will help prevent particle aggregation, thereby improving the stability of the dispersion. In addition, high concentrations of nano-hydroxyapatite particles will occupy more space, thereby providing a physical barrier for each particle, reducing the possibility of direct contact and aggregation between particles, and enhancing the stability of the dispersion. However, due to the limits of Brownian motion and stability of particles, when the nano-hydroxyapatite particles increase to a critical concentration, the random motion of the particles increases, the chance of collision between particles increases, and they are prone to aggregation, resulting in sedimentation, which reduces the stability of the dispersed system. Figure 2 Observing the daily precipitation and optical density, the effect of comparative example 4 is the best; however, according to Figure 2 It can be seen from the broken line in (A) that the dispersion amount of nano-hydroxyapatite particles in the dispersion liquid in Examples 2 to 3 is the highest. Therefore, in general, the dispersion liquid of Examples 2 to 3 has the best effect.

[0028] (3) pH value screening The dispersions of Example 1 and Comparative Examples 6 to 8 were subjected to zeta potential, UV spectrum and peak loss rate tests. The zeta potential was measured using a zeta potential analyzer, and the UV spectrum was measured using a UV-visible spectrophotometer. The results are shown in Figure 3 .

[0029] The larger the absolute value of the dispersion Zeta potential, the better the dispersion and the more stable the dispersion. Figure 3It can be seen that the absolute value of the zeta potential of the dispersion of Example 1 is the highest. With the increase of pH, the ultraviolet peak of the CMC / nHAP dispersion first increases, then decreases, and then increases again. The peak first blue-shifts, then red-shifts, and then red-shifts. The ultraviolet peak of the CMC / nHAP suspension at different pH values ​​decreases with the increase of the stabilization time, and the loss of the highest peak first increases and then decreases with the increase of pH. When pH=4, the CMC / nHAP dispersion becomes clear, nHAP dissolves in the acidic solution, and the ultraviolet peak loss rate is 7.1%; when pH=8, the ultraviolet peak loss rate of the CMC / nHAP suspension is 20.0%; when pH=12, the ultraviolet peak loss rate of the CMC / nHAP suspension is 16.0%. When pH=9, the ultraviolet peak loss rate of the CMC / nHAP suspension is 12.0%. Comprehensive analysis shows that although the peak loss is the smallest at pH=4, nHAP is dissolved, so the optimal dispersion pH is 9, and the dispersion effect is the best. In terms of Zeta potential, UV peak change and peak loss rate, Example 1 has the best stability.

[0030] (4) Dispersion hydraulic diameter Dynamic light scattering DLS was used to measure the hydrodynamic diameter of the dispersions of Example 1 and Comparative Examples 9 to 11. The results are shown in Figure 4 .

[0031] The hydrodynamic diameter is an important parameter that describes the apparent size of particles in solution due to Brownian motion, and is also an important parameter for measuring the stability of dispersions. Figure 4 It can be seen that, compared with Example 9, the treatment conditions of Example 1 are the same, but the particle size of the nanohydroxyapatite particles is different. It can be seen that the hydraulic diameter of the nanohydroxyapatite with a small particle size decreases more under CMC dispersion. Compared with Example 10, the hydraulic diameter of the nanohydroxyapatite with the same particle size treated with CMC is smaller than that of the nanohydroxyapatite without CMC treatment, which is reduced by 99.8%. Therefore, CMC improves the stability of nanohydroxyapatite, and small-sized nanohydroxyapatite is more conducive to CMC dispersion of nanohydroxyapatite.

[0032] Test Example 2: Application Test (1) Removal of cadmium pollution The dispersions prepared in Example 1 and Comparative Example 10 were subjected to a cadmium pollution removal test, with a 0.5wt% CMC aqueous solution as a control example. The specific method is: 10mL of a 100mg / L cadmium solution (cadmium nitrate aqueous solution) was added to 30mL of the dispersions prepared in Example 1 and Comparative Example 10, respectively, and reacted under a constant temperature shaker at 25°C, and samples were taken at fixed times of 30min, 60min, 120min, 180min, 300min, 480min, 720min, and 1440min. The residual cadmium concentration in the filtrate was determined by flame atomic absorption spectrophotometry, and the cadmium adsorption amount = (cadmium initial concentration - cadmium equilibrium concentration) * solution volume / adsorbent mass, and the results are as follows Figure 5 And as shown in Table 2.

[0033] Table 2 Adsorption amount of cadmium It can be seen from Table 2 that compared with nHAP (Comparative Example 10), nHAP treated with CMC (Example 1) has a stronger ability to adsorb cadmium.

[0034] (2) Promote plant growth The dispersion prepared in Example 1 and Comparative Example 10 was used as a phosphate fertilizer for pepper foliage, and a 0.5wt% CMC aqueous solution was used as a control example. Pepper seedlings were first raised in a plant incubator. When the pepper leaves grew to 6-7 leaves, they were transplanted into potted plants for testing. Two weeks after transplanting, the dispersions of Example 1 and Comparative Example 10 were sprayed onto the pepper leaves, with 5 mL / plant sprayed once a week for a total of 5 times. An equal amount of clean water was used as the CK group, and 5 plants in each group were used as parallel tests. The pepper fruits were harvested 2 months after transplanting, and the fruit volume of the peppers was tested by the drainage method, and the average fruit volume of the peppers was calculated. The results are shown in Figure 6 .

[0035] according to Figure 6 It can be seen that the pepper fruit volume obtained in Example 1 group is the largest, indicating that nHAP treated with CMC can promote pepper growth when used as a fertilizer.

[0036] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A nano-hydroxyapatite dispersion, characterized in that: The nano-hydroxyapatite dispersion is prepared by the following method: The sodium carboxymethyl cellulose solution was slowly added to the nano-hydroxyapatite solution, and stirred at room temperature. The pH was adjusted to 9.0, and heated for reaction to obtain a nano-hydroxyapatite dispersion.

2. The nano-hydroxyapatite dispersion according to claim 1, characterized in that: The sodium carboxymethylcellulose solution is obtained by dissolving sodium carboxymethylcellulose powder in water and heating it at 50-60° C.; the nano-hydroxyapatite solution is obtained by dispersing nano-hydroxyapatite in water and subjecting it to ultrasonic treatment.

3. The nano-hydroxyapatite dispersion according to claim 2, characterized in that: The particle size of the nano-hydroxyapatite is 60 nm.

4. The nano-hydroxyapatite dispersion according to claim 1, characterized in that: The volume ratio of the sodium carboxymethyl cellulose solution to the nano-hydroxyapatite solution is 1:1; and the stirring time is 3 hours.

5. The nano-hydroxyapatite dispersion according to claim 5, characterized in that: The mass concentration of the sodium carboxymethyl cellulose solution is 0.5wt%; the concentration of the nano-hydroxyapatite solution is 0.3g / L-0.6g / L.

6. The nano-hydroxyapatite dispersion according to claim 1, characterized in that: The method for adjusting pH is to add alkali solution; the alkali solution is NaOH solution, and the concentration of the NaOH solution is 0-0.3 mol / L.

7. The nano-hydroxyapatite dispersion according to claim 1, characterized in that: The heating reaction is carried out at a temperature of 40-60° C. and for a time of 30-60 min.

8. Use of the nano-hydroxyapatite dispersion according to any one of claims 1 to 7 in any one of the following 1) to 3): 1) Improve the stability of nano-hydroxyapatite dispersion; 2) Adsorption of cadmium ions; 3) Promote plant growth.

9. The use according to claim 8, characterized in that: The method of improving the stability of the nano-hydroxyapatite dispersion includes: improving the dispersibility of the nano-hydroxyapatite, reducing the hydrodynamic diameter of the nano-hydroxyapatite, and increasing the absolute value of the zeta potential of the nano-hydroxyapatite.

Citation Information

Patent Citations

  • Three-dimensional porous nanometer hydroxyapatite and preparing method thereof

    CN106927443A

  • Nanometer hydroxyapatite dispersion body and preparation process thereof

    CN107555406A

  • Synthesis of biomimetic and high strength biopolymer / hydroxyapatite composites

    KR101840621B1

  • Dispersion

    WO2021246373A1

  • Hydroxyapatite microsphere having adjustable morphology and size, and preparation method therefor

    WO2024001298A1